Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan terhadap Kinerja Pegawai Melalui Disiplin Kerja Sebagai Variabel Intervening - Hadi, Iqbal Setio; Sari, Vivi Nila; Pratiwi, Nila (Jurnal Ekonomi & Bisnis, 2024)
Human resources are the most important thing to pay attention to because in human hands company goals can be achieved well, human resources play an active role in every company activity, basically humans are planners, actors and help realize organizational goals that have been planned and set by having good performance quality.This study aims to examine how much influence the work environment and leadership style have on employee performance with work discipline as an intervening variable at the Solok Regency Regent's Office. Data collection methods through surveys and circulating questionnaires, with a sample of 40 respondents. The analysis method used is path analysis using smartpls. The results of the research obtained The work environment has a positive and insignificant effect on employee performance. The work environment has a positive and significant effect on work discipline. Leadership style has a positive and insignificant effect on employee performance. Leadership style has a positive and significant effect on work discipline. Work discipline has a positive and insignificant effect on employee performance. Work environment has a positive and insignificant effect on employee performance through work discipline as an intervening variable. Based on the results of this study, it is hoped that agency management can improve employee performance by paying more attention to and improving the work environment, leadership style, and work discipline at the Solok Regency Regent's Office through each indicator.